2008
DOI: 10.1007/s10534-008-9136-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization of some transition metal(II) complexes of acetone p-amino acetophenone salicyloyl hydrazone and their anti microbial activity

Abstract: Complexes of the type [M(apash)Cl] and [M(Hapash)(H2O)SO4], where M = Mn(II), Co(II), Ni(II), Cu(II) and Zn(II); Hapash = acetone p-amino acetophenone salicyloyl hydrazone have been synthesized and characterized by elemental analyses, molar conductance, magnetic moments, electronic, ESR and IR spectra, thermal studies (TGA & DTA) and X-ray diffraction studies. The ligand coordinates through two >C=N and a deprotonated enolate group in all the chloro complexes, whereas through two >C=N- and a >C=O group in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…The minor shifted position of ν(C-N) bands in the metal complexes as compared to the ligands also support the non-involvement of the two amide >C=O groups in bonding. However, the other ν(C=O) band due to indole >C=O group is considerably shifted to lower frequency by 19-23 cm −1 in all ismdh complexes, indicating the participation of indole >C=O group in bonding with metal 35 . The disappearance of ν(C=O) of indole ring in all the isodh complexes suggests the enolization of indole ring >C=O group during complexation ( Table 6).…”
Section: Ir Spectramentioning
confidence: 85%
“…The minor shifted position of ν(C-N) bands in the metal complexes as compared to the ligands also support the non-involvement of the two amide >C=O groups in bonding. However, the other ν(C=O) band due to indole >C=O group is considerably shifted to lower frequency by 19-23 cm −1 in all ismdh complexes, indicating the participation of indole >C=O group in bonding with metal 35 . The disappearance of ν(C=O) of indole ring in all the isodh complexes suggests the enolization of indole ring >C=O group during complexation ( Table 6).…”
Section: Ir Spectramentioning
confidence: 85%
“…Unfortunately, these experiments also indicated that the cobalt(III) cylinders are not active antimicrobial agents, and no inhibition of bacterial growth was observed over a range of concentrations, from 1024 µg·mL −1 to 1 µg·mL −1 . Given the stability of the [Co 2 (L pytrz ) 3 ](OTf) 6 cylinders in aqueous and pseudo-biological conditions and the activity of other triply stranded helicates [13,18], related dinuclear ruthenium(II) compounds [53,57], and cobalt(III) complexes [41,42], the observed lack of activity was initially surprising. However, a series of elegant papers from Keene and co-workers have shown that the charge of the metal complex is an important factor for obtaining active antimicrobial complexes.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Cobalt is a physiologically active metal that has key functions in many biological processes [37]. Because of this, more and more cobalt complexes are being explored for an extensive range of biological applications such as anti-inflammatory [38], antiviral [39], anticancer [40], and antimicrobial [41,42] agents amongst others [43]. Consequently, development of cobalt complexes could significantly enhance the arsenal of pharmaceutical drugs available to combat a wide variety of harmful diseases and reduce antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in the study of hydrazone compounds and their metal complexes has recently been grown up due to their biological activities as antifungal, 1-3 antibacterial [1][2][3][4] anticonvulsant, 5 anti-inflammatory, 3 anti-malarial, 6 analgesic, 7 anti-platelets, 8 anti-tuberculosis, 9 anticancer, 10 and a treatment of leprosy and mental disorder diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral and elemental analyses indicated that, the hydrazone ligands behave as neutral bidentate (H 2 L 1-2 ), monobasic bidentate (HL [1][2] ) or monobasic tridentate ligands toward the metal ions, bonded with the metal ion via protonated or deprotonated phenolic hydroxyl oxygen atom, azomethine nitrogen atom or ketonic carbonyl oxygen atom.…”
mentioning
confidence: 99%